Access and rational use of psychotropic medications in low- and middle-income countries. (21st September 2015) - Padmanathan, P.; Rai, D.
Abstract : Improving access and rational use of psychotropic medications in low- and middle-income countries is an important factor in reducing the public health burden resulting from mental illness. This paper considers each component of the medications management cycle to identify current barriers to improvement. Selection is hindered by a lack of up to date local essential drugs lists, while procurement and distribution can be affected by the type of system used: centralised or decentralised, government-run or independent, push or pull. Rational use involves patients, prescribers and policy-makers and requires consideration of who is able to prescribe, how prescribing decisions are made and how to ensure patient-centred care. We include a number of recommendations based on these issues, while emphasising the importance of ensuring the broader context of mental illness and its management is not overlooked when improving access to psychotropic medications.